Pengaruh Rasio Keuangan Terhadap Pertumbuhan Laba pada Perusahaan Sektor Pertambangan yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2023 (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is a quantitative study aimed at analyzing the effect of financial ratios on profit growth in mining sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2023 period. The research sample was obtained using a purposive sampling method, where only 19 mining sector companies listed on the IDX met all criteria, resulting in 76 data points used as the research sample. The independent variables of this study consist of liquidity ratios measured by CR, solvency ratios measured by DER, activity ratios measured by TAT, and profitability ratios measured by NPM, ROA, and ROE. This study employs data analysis techniques in the form of multiple linear regression analysis using panel data with the aid of Eviews 12 software. Based on the hypothesis, the research results show that CR, TAT, NPM, ROA, and ROE do not have a positive and significant effect on profit growth, while DER has a negative and significant effect on profit growth.